Order Form and Information in Securities Markets - EASLEY, DAVID; O'HARA, MAUREEN (Journal of Finance, 1991)
ABSTRACT This paper examines the effects of price‐contingent orders on security prices. We show that a market maker who knows the type and composition of trades will set larger spreads and adjust prices faster than if price‐contingent orders were not allowed. Because traders have rational expectations over the book, we demonstrate that uncertainty over order type reduces the variance of prices but with a corresponding loss in price informativeness. We also show that the sequence property of price‐contingent orders increases the probability of large price movements. This distinction between variance and episodic price volatility has important policy implications.